DESIGN OF A WEB-BASED GEOGRAPHIC INFORMATION SYSTEM (GIS) FOR MAPPING OF THE ZEE STUDIO ARCHITECT PROJECT. - Davit Hermawan; Nurdiansyah; Endra Abdul Hadi (Politeknik Mardira Indonesia, 2026)
This research aims to design and implement a web-based Geographic Information System (GIS) as a portfolio and project monitoring tool at Zee Studio. The main problems encountered were the difficulty in visualizing dynamic project distribution and limited access to spatial documentation. This system was developed using Agile development methods with a Scrum approach, which allows for rapid and adaptive feature iteration. The technologies used include PHP (MySQLi), JSON, and the Leaflet.js library for digital map management. Through several Sprint cycles, the system successfully integrated mapping features with project status indicators, automatic statistics, and multimedia information pop-ups that support narrative descriptions and photo galleries. Test results showed that the Agile approach was effective in producing a responsive system, secure from SQL Injection vulnerabilities, and able to increase marketing conversions through the integration of Meta Ads Pixel and WhatsApp API.